Peningkatan Berkomunikasi dan Hasil Belajar Bahasa Indonesia dengan Strategi Problem Based Learning Di SMA - Suryani, Esti (Universitas Muhammadiyah Surakarta, 2015)
This research has a purpose trough BBPL strategic could improve communication and Bahasa Indonesia studying result for students X MIA-3 grade semester 2013/2014. This research is a action class research which has two cyclone and each of cyclone contain 4 steps, action planning, action doing, observation, and reflection. Subject of this research are the 41 students of X MIA-3 grade SMA Batik 1 Surakarta. Collecting data by observation with observation sheet and written test technique questions within. Collected data sort by table form graph and analysis. Data analysis in this research used descriptive comparative technique. Total student pass KKM before action are 5 students (19%), first cyclone increase 20 students (49%) and second increase 34 students (85%). Research result is implementation BPL strategic could improve communication and Bahasa Indonesia studying result persuade chapter for student X MIA-3 grade. Summary of this research is implementation PBL learning strategic in Bahasa Indonesia learning could increase communication and Bahasa Indonesia studying result for students.